A study on the effects of road humps in reducing speed along local roads in residential areas: case study of Taman Setiawangsa - Ahmad Sofi, Siti Syazwani; Kadar Hamsa, Abdul Azeez (Malaysian Institute of Planners, 2016)
The increasing number of vehicles along local roads in many residential areas has created unconducive environment and safety risk due to the increase in the speed passing vehicles. To control the speed of the vehicles, road humps were installed along local roads. This paper evaluates the effects of road humps on the speed of vehicles in Taman Setiawangsa, which is one of the residential areas in Kuala Lumpur. The field observational survey was carried out to collect data on design characteristics of the road humps. A spot speed survey was administered to collect spot speed of vehicles at different points near the road humps and the spot speed data at and near road humps were analysed using measures such as descriptive statistics and dependent t-Test. The design characteristics of the road humps were also compared with the existing road hump guidelines published by the authorities. The major finding of this study depicts the effectiveness of road humps in reducing speed in relation to the road hump’s profiles.